2021
DOI: 10.3390/toxics9030046
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Biophysical Linkages between Coastal Forestry Management Practices and Aquatic Bivalve Contaminant Exposure

Abstract: Terrestrial land use activities present cross-ecosystem threats to riverine and marine species and processes. Specifically, pesticide runoff can disrupt hormonal, reproductive, and developmental processes in aquatic organisms, yet non-point source pollution is difficult to trace and quantify. In Oregon, U.S.A., state and federal forestry pesticide regulations, designed to meet regulatory water quality requirements, differ in buffer size and pesticide applications. We deployed passive water samplers and collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Scully-Engelmeyer et al (2021) have measured 12 pesticides including herbicide, fungicide, and insecticide, in bivalve samples. 36 They reported that they could detect indaziflam even in the forest. 36 In another study, Sun et al (2018) reported that indaziflam caused root mass changes in hybrid Bermuda grass and decreased accumulation of macro/ micro-nutrients in roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scully-Engelmeyer et al (2021) have measured 12 pesticides including herbicide, fungicide, and insecticide, in bivalve samples. 36 They reported that they could detect indaziflam even in the forest. 36 In another study, Sun et al (2018) reported that indaziflam caused root mass changes in hybrid Bermuda grass and decreased accumulation of macro/ micro-nutrients in roots.…”
Section: Discussionmentioning
confidence: 99%
“…36 They reported that they could detect indaziflam even in the forest. 36 In another study, Sun et al (2018) reported that indaziflam caused root mass changes in hybrid Bermuda grass and decreased accumulation of macro/ micro-nutrients in roots. 37 As a result, the present study focused on filling a gap related to cytotoxicity and genotoxicity of indaziflam on HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2017 and 2018, individual biological samples of M. falcata were collected as part of an assessment of bivalve pesticide contaminants (Scully-Engelmeyer et al, 2021). These samples originated from seven Coast Range watersheds (eight total collection sites).…”
Section: Mussel Condition Samplingmentioning
confidence: 99%